2015
DOI: 10.16966/2381-5299.107
|View full text |Cite
|
Sign up to set email alerts
|

The Use of (Treated) Domestic Wastewater for Irrigation: Current Situation and Future Challenges

Abstract: The use of treated, diluted, and even raw domestic wastewater for agricultural irrigation is becoming an essential component of a more sustainable and integrated water resources management, especially in water-scarce regions. More than 20 million hectares are currently being irrigated with wastewater worldwide by about 200 million farmers. This paper provides an overview of some developments in the field of water reuse in agriculture, with a specific focus on Latin America, where this practice is rapidly growi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 117 publications
0
3
0
1
Order By: Relevance
“…Application of wastewater weather treated, raw, inadequately treated or thinned for irrigation purposes is a common practice in rural and urban areas [98]. Water scarcity in certain regions of the world such as sub-Saharan Africa amidst other factors like too much dependability of limited water source, proximity to a water source and the availability of nutrients has forced so many farmers to resort to the use of wastewater for the irrigation of fresh produce.…”
Section: Preharvest Transmission Routes Of Fresh Produce Associatementioning
confidence: 99%
See 1 more Smart Citation
“…Application of wastewater weather treated, raw, inadequately treated or thinned for irrigation purposes is a common practice in rural and urban areas [98]. Water scarcity in certain regions of the world such as sub-Saharan Africa amidst other factors like too much dependability of limited water source, proximity to a water source and the availability of nutrients has forced so many farmers to resort to the use of wastewater for the irrigation of fresh produce.…”
Section: Preharvest Transmission Routes Of Fresh Produce Associatementioning
confidence: 99%
“…(11 to 1.4 × 10 4 CFU/100 mL) [99]. However, adequate treatment of wastewater is only done in a few cases because the procedure is costly and time overwhelming [98]. Studies have indicated that only about 10% of wastewater is treated adequately in growing countries [13].…”
Section: Preharvest Transmission Routes Of Fresh Produce Associatementioning
confidence: 99%
“…Concerning other experiences, the identification of reliable and feasible areas for treated wastewater irrigation has a positive impact on the overall water balance and slightly reduces the water "footprint" of agriculture (Hoekstra et al 2011), even if the impact is mostly near urban areas. The identification of reliable areas could also contribute to a healthy impulse of new norms and policies, especially given the context in most Latin American countries, where lack of legislation, deficits in sanitation infrastructure, and weak governmental institutions support unplanned and informal reuse schemes, thus intensifying the negative effects of the practice (Gatto et al 2015).…”
Section: Scenario Analysismentioning
confidence: 99%
“…Cette forte minéralisation est due à une richesse en minéraux de divers déchets provenant des activités anthropiques et également à la concentration de ces minéraux résultant de l'évaporation d'une partie de l'eau en saison sèche. Les TDS, quant à eux, permettent de connaître la quantité de matières dissoutes des éléments tels que le calcium, le magnésium, le sodium, les chlorures et les sulfates (Ndinwa et al, 2012). Les valeurs du TDS des eaux évoluent dans le même sens que la conductivité.…”
Section: Contamination Des Eaux Usées Et Des Légumes Par Les Coliformesunclassified